Drivers and outcomes of salespersons' value opportunity recognition competence in solution selling. Issue 3 (2nd July 2020) - Böhm, Eva; Eggert, Andreas; Terho, Harri; Ulaga, Wolfgang; Haas, Alexander
Abstract: In B2B markets, firms seek to provide customer solutions instead of merely selling goods or services. As boundary-spanners, salespeople are pivotal for implementing this strategic shift. Yet, extant literature provides limited insights into salesperson's resources and competencies required for customer solutions, particularly in the early phases of solution selling. This research focuses on salesperson's value opportunity recognition competence (VOR), which is a central requirement for salespeople to be able to navigate the early phases of solution selling. Analyzing large-scale, multi-level data of 799 salespeople and their respective sales managers in 29 sales organizations, the authors investigate the role of different salesperson resources and work environment characteristics for strengthening their VOR. The authors find that salespeople need both customer and technical knowledge, but customer knowledge is more important. Salespeople also can substitute individual technical knowledge with strong internal relations, but strong customer relations are no substitute for individual knowledge about customers' business models and processes. Formalization turned out to be a double-edged sword in the context of VOR development, while transformational leadership has positive effects only. The findings bear concrete implications for improving the selection, training, and work environment of solution salespeople.